The Influence of Covid-19 on Business Sustainability with Corporate Action as a Moderation Variable - As'ari, Hasim; Astuti, Tutut Dewi; Suarsa, Abin (Universitas Mercu Buana, 2025)
Objectives: This study aims to test: 1) the influence of Covid-19 on Business Sustainability; 2) the influence of Covid-19 on Business Sustainability with Corporate Action as a moderation.Methodology: This study uses secondary data. The sampling method uses purposive sampling. The sample used was 32 companies listed on the IDX that carried out corporate actions in 2020. Hypothesis testing 1 and 2 used the t-test. Hypothesis testing 3 used the F test because it contains elements of interaction between two.Finding: The results of the Covid-19 study proxied by ROE did not show an effect on business sustainability, while those proxied by Current Ratio showed an effect on business sustainability. The Covid-19 and Corporate Action variables as moderating variables jointly affect business sustainability.Conclusion: The impact of Covid 19 and corporate actions have an important role and have been proven to jointly affect business sustainability. Liquidity needs to be maintained to ensure that business sustainability runs effectively considering the impact of Covid-19. On the other hand, profitability does not affect business sustainability, because cash flow is not smooth, where cash flow is a source of business sustainability. Corporate action policies to attract interest and restore investor confidence in the company amidst the spread of Covid-19, thus impacting business sustainability.